Integrating Multiple Intelligences into Social Studies Instruction: A Conceptual Framework for Enhancing Holistic Learning in Elementary Education - Vera Feryyal (Sustainable, 2026)
This study aims to explore the integration of Multiple Intelligences (MI) into Social Studies learning at the elementary school level through a qualitative literature review. By synthesizing [insert actual number] relevant scholarly articles published between 2020 and 2025, this study examines how MI-based instructional models can enhance holistic student development. The findings reveal that traditional Social Studies instruction, which often emphasizes memorization, is insufficient in addressing the diverse cognitive, affective, and social needs of students. In contrast, the integration of Multiple Intelligences provides a more inclusive and student-centered learning approach by accommodating various learning styles and potentials. Furthermore, MI-based learning is found to support the development of critical thinking, empathy, collaboration, and social responsibility, key competencies required in 21st-century education. Instructional strategies such as problem-based learning, inquiry-based learning, and project-based learning are identified as effective approaches for implementing MI in Social Studies classrooms. However, the study also highlights challenges related to teacher readiness, limited resources, and curriculum constraints. Therefore, successful implementation requires professional development, curriculum adaptation, and institutional support. Overall, this study contributes to the development of a conceptual framework for integrating Multiple Intelligences into Social Studies learning to promote more meaningful and holistic educational outcomes.